COMPLICATIONS OF NOSE AND PARANASAL SINUS DISEASE - Sajid, Tahira; Kazmi, Hasan Sajid; Shah, Shahid Ali; Ali, Zulfiqar; Khan, Farida; Ghani, Rehman; Khan, Jaffar (Journal of Ayub Medical College Abbottabad, 2011)
Background: Diseases of nose and paranasal sinuses can complicate to involve the orbit and other surrounding structures because of their close proximity. These diseases are usually infective or can be neoplastic in origin. Method: All the patients presenting in ENT or Eye Departments of Ayub Teaching Hospital during the one year study period who had complicated nose or paranasal sinus disease were included in the study. A detailed history and examination followed by CT scanning and laboratory investigations to assess the type and extent of the disease, was carried out. Results: Infections were the most common cause of complicated sinus disease 11 (75%). The rest of the 4 (25%) cases were tumours. 12 (80%) of the cases presented with proptosis. In 1 of these 12 cases, there was complete blindness. In 2 (13%) of the cases there was only orbital cellulitis. Two of these patients had facial swelling and 2 had nasal obstruction and presented as snoring. Two patients presented with history of weight loss and these patients had malignant tumour of the paranasal sinuses. One patient presented with early signs of meningitis. In 1 case subperiosteal scalp abscess (Pott's puffy tumour) was the only complication noted. Conclusion: Nose and paranasal sinus diseases can complicate to involve mostly the orbit, but sometimes brain, meninges and skull bones can also get involved. Keywords: Paranasal sinuses, orbital complications, complicated sinus disease, Pott's puffy tumour